Bacterioplankton dynamics in the Mondego estuary (Portugal) - Bacelar-Nicolau, P. (2003)
In this work, the density of bacterioplankton and environmental parameters were monitored over a 11 month period (July 1999-June 2000), and also during one tidal cycle (15 June 2000), at two sampling stations, in the estuary of River Mondego. These data were treated by multivariate analyses methods in order to identify the key factors that control the dynamics of the bacterioplankton in the estuary. Bacterial dynamics were dominated by temporal gradients (annual seasons and tide-related) and less by the spatial structure of the estuary. Three main metabolic groups of bacterioplankton--aerobic heterotrophic bacteria, sulphate-reducing bacteria (SRB) and nitrate-reducing bacteria (NRB)--involved in the cycling of organic matter, were present in the water column of the estuary. Their relative abundance depended on the particular physical, chemical and biological environment. The abundance of aerobic heterotrophic bacteria, during the 11 month study, was modelled as a function of nitrate (the most important variable, with a negative effect), temperature, salinity and pH (with positive effects). SRB appeared to be limited to the water-sediment interface, where concentrations of sulphate and POM were greater. A competition between SRB and NRB for carbon has also been suggested.